ANALISIS RASIO KEUANGAN DALAM MEMPREDIKSI KINERJA KEUANGAN (Studi Pada Perusahaan Food dan Beverages Di Bursa Efek Indonesia) - R.Gatot Heru Pranjoto (InFestasi, 2013)
The aims of this research is to investigate the influence of financial ratio to net income (NI) in both simultaneous or partial way. The unit analysis and research population is Food and Beverage manufacture companies listed in Indonesia Stock Exchange (BEI) during the period of 1 January 2006 until 31 December 2009. Sampling technique used is purposive sampling. Whether the analysis techniques used is multiple regression.The research findings show that independent variable models (DR, ROA, NWC, ROE, TAT, and OPM) have tolerant value of under 15%. This suggests that 85% of each independent variable (DR, ROA, NWC, ROE, TAT, and OPM) can be explained by other predictors (independent variables). The ANOVA or F-Test results shows that the F-value is 77.82 with significant value of 0.000. Simultaneously, financial ratio measured by DR, ROA, NWC, ROE, TAT, and OPM affect net income (NI). From the six independent variables, it has been found correlation value among variables is quite high that is above 0.5, suggests that there is multicollnearity or correlation among the six variables. The significance of one side correlation of the output (measured from probability) results in variety value, where variable DR, ROA, NWC, ROE, TAT, and OPM have strong correlation significance, whether the other four variables (DTE, ITO, NPM, and CR) were not correlated significantly.